Influence of total histerectomy on pelvic prolapse and urinary incontinence - Szmuklerz-Kajdos, Elżbieta; Lau, Katarzyna; Wieczorek, Marek; Puto, Wojciech; Bobeff, Artur; Rutkowska, Beata (Menopause Review/Przegląd Menopauzalny, 2009)
Aim: Pelvic organ prolapse are related with anterior, posterior, fornix colpoptosis or uterus prolaps and is frequently connected with low urinary tract dysfunction. Objective: The aim of the study was to estimate influence of hysterectomy on pelvic organ prolapse and urinary incontinence. Material and methods: In our research we included 38 women after hysterectomy, administered to gyneacological examination and urodynamic diagnostics. Results: In our group 47% presented pelvic organ prolapse and 42% urinary incontinence. Conclusions: Hysterectomy is a risk factor of pelvic organ prolapse and urinary incontinence-stress urinary incontinence is the most common incontinence type after hysterectomy.